Simulation and analysis of surface plasmon resonance based sensor - Lourenço, Paulo (2019)
In this paper, we will be presenting the results obtained through Finite-Difference Time Domain simulations on a photonic sensing architecture. This device consists on a dielectric/metal/dielectric sensing structure. Under adequate conditions, when electromagnetic energy strikes the different dielectrics interface, these devices develop surface plasmon resonances which are extremely sensitive to refractive index variations, thus being able to be used as sensing structures. Considering their minute dimensions, monolithic integration is attainable and by incorporating cost-effective materials in their manufacture, devices' mass production may be efficient and information and communication technological systems' resiliency will be greatly facilitated. Next, this architecture is analysed under amplitude and refractive index sensitivity perspectives, its performance is analysed and considerations about its use as a sensing device are contemplated. Finally, conclusions of our work are presented and future development directions are described.